MITIGASI BENCANA PERKAWINAN ANAK SEBAGAI UPAYA MEWUJUDKAN KELUARGA SAKINAH: PERSPEKTIF FIKIH PERLINDUNGAN ANAK - Marwa, Muhammad Habibi Miftakhul (Faculty of Law, Parahyangan Catholic University, 2021)
Child marriage, in the final analysis, is denial of childrens basic right. The practice also violates the prevailing law which sets a statutory age limitation for both men and women to marry at 19 years. The author seeks to analyse this legal-societal issue from Islamic law perspective. The analysis starts from the general observation that to prevent future dissent-disolvement of marriages, both parties should consider “rusyd”, in other words, their own or potential partners psychological, biological, and socio-economic maturity. In addition, to prevent child marriage, attention should be given to basic values of benefit (al mashlalah), the general principle of affection (mawaddah wa rahmah) and fulfillment of needs (taufir al-hajat).